2021
DOI: 10.1016/j.sdentj.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of experimental ZnO cement containing niobophosphate bioactive glass as filling temporary material

Abstract: Aims The aim of this study was to develop and characterize a temporary restorative material based on a zinc oxide matrix containing niobophosphate bioactive glass (NbG) for the caries-affected dentin treatment. Material and methods NbG was added to a ZnO 2 matrix in different concentrations (wt%). EDS-SEM, ATR-FTIR and XRD analyses were performed to characterize the cement. Calcium release was evaluated in TRIS solution after 1, 7 and 14 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…These results are in accordance with previous studies conducted by Ferreira et al, who concluded that the addition of at least 10% niobophosphate bioactive glass to ZOE enhances its compressive strength compared to unmodified ZOE cement [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with previous studies conducted by Ferreira et al, who concluded that the addition of at least 10% niobophosphate bioactive glass to ZOE enhances its compressive strength compared to unmodified ZOE cement [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The sample size calculation was based on a similar study [ 37 ]. With an alpha level of 0.05 and a power of 85%, a sample size was determined using G*Power software version 3.1.9.7 (Heinrich Heine University Duesseldorf, Duesseldorf, Germany).…”
Section: Methodsmentioning
confidence: 99%